PTH: Redefining Reference Ranges in a Healthy Population—The Role of Interfering Factors and the Type of Laboratory Assay - Simona Censi; Maurizio Iacobone; Stefano Simmini; Jacopo Manso; Giulio Franceschet; Mario Plebani; Anna Chiara Frigo; Martina Zaninotto; Francesca Torresan; Giustina De Silvestro; Carla Scaroni; Caterina Mian; et al. (International Journal of Endocrinology)
Introduction. Parathyroid hormone (PTH) is a linear peptide constituted by 84 amino acids and active in its 1–84 form, but a wide range of PTH forms produced by its post-transcriptional modifications are present in blood. Many assays with different specificities are commercially available. The aim of our study was to compare a 2nd and 3rd generation in healthy population in order to better define the reference range in the healthy population residing in our region. Materials and Methods. 108 subjects (53 females and 55 males) referring to the transfusion donor were enrolled in the study centre in April 2016 and underwent PTH levels measurements with a 3rd generation kit (chemiluminescent immunoassay DiaSorin Liaison) and with a 2nd generation kit (immunoradiometric assay Total Intact PTH Assay (Coated Tube), Scantibodies). Also calcium, phosphate, creatinine, and 25OHD3 were measured. A questionnaire on lifestyle and dietary habits was obtained. Results. The median PTH values obtained with the 2nd generation assay and the whole 3rd generation assay were 20.26 pg/ml and 23.11 pg/ml, respectively. Bland–Altman method showed substantial concordance between the two PTH assays, although with an overestimation of the 3rd generation method over the 2nd generation method. There was no correlation between 3rd generation PTH and 25OHD3 and creatinine. Calcium was negatively correlated with PTH only when measured with 3rd generation kit. Conclusions. On the basis of our data, obtained from healthy subjects, we can conclude that the reference range used by our laboratory was too narrow and was necessary to reestablish normal ranges according to our population. This is useful to avoid hyperparathyroidism misdiagnosis.